Answer:
x = 65
y = 11.25
Step-by-step explanation:
The given system of equation is:
4y = 2x - 85 ............> equation I
x - 4y = 20
which can be rewritten as:
4y = x - 20 ...........> equation II
Bow, multiply equation II by 2, we will get the following:
8y = 2x - 40 .........> equation III
Subtract equation I from equation III to eliminate the x and solve for y as follows:
8y = 2x - 40
- (4y = 2x - 85)
-------------------------------
4y = 0x + 45
Therefore:
4y = 45
y = 45/4
y = 11.25
Now, substitute with the value of y in equation I to get x as follows:
4y = 2x - 85
4(11.25) = 2x - 85
45 = 2x - 85
2x = 130
x = 130/2
x = 65
Hope this helps :)